2008
DOI: 10.1111/j.1462-2920.2007.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of β‐N‐methylamino‐l‐alanine, a neurotoxic amino acid with other cyanobacterial toxins in British waterbodies, 1990–2004

Abstract: The neurotoxic amino acid, beta-N-methylamino-L-alanine, was found to be present in all of 12 analysed samples of cyanobacterial blooms, scums and mats, which had been collected in seven years between 1990 and 2004 inclusive and stored at -20 degrees C. BMAA identification was by high performance liquid chromatography with fluorescence detection and by triple quadrapole mass spectrometry after derivatization. The samples originated from 11 freshwater lakes and 1 brackish waterbody, used either for drinking wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
7
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(179 citation statements)
references
References 33 publications
4
167
7
1
Order By: Relevance
“…This combination of BMAA detection with HPLC or UPLC coupled with mass spectrometric verification of the BMAA peak reconfirms HPLC or UPLC detection of BMAA in a sample [8,11,12,19]. We used two different spectrometric techniques to verify the BMAA peak in the CCMED-01 marine Nostoc sp.…”
Section: B Chromatographic and Spectrometric Determination Of Bmaa mentioning
confidence: 99%
“…This combination of BMAA detection with HPLC or UPLC coupled with mass spectrometric verification of the BMAA peak reconfirms HPLC or UPLC detection of BMAA in a sample [8,11,12,19]. We used two different spectrometric techniques to verify the BMAA peak in the CCMED-01 marine Nostoc sp.…”
Section: B Chromatographic and Spectrometric Determination Of Bmaa mentioning
confidence: 99%
“…Metcalf et al (2008) identified MC, anatoxin-a, nodularin and saxitoxin in a number of British surface waters in addition to BMAA. Al-Sammak et al (2014) reported an association of BMAA with MC in Nebraska reservoirs.…”
Section: Discussionmentioning
confidence: 98%
“…The ubiquitous distribution of BMAA provides a multiplicity of potential routes for human exposure from drinking water (Metcalf et al, 2008;Bradley et al, 2013), bathing and showering, and consumption of aquatic foodstuffs, as well as dietary supplements that incorporate certain "edible" cyanobacteria (e.g. Nostoc www.ccsenet.org/ep Environment and Pollution Vol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, BMAA was found in the cyanobacterium Nostoc living in symbiosis with this cycad [32]. This first report of BMAA in a cyanobacterium was followed by positive reports for BMAA in free living and symbiotic cyanobacteria, as well as in cyanobacteria dominated field samples [33][34][35][36]. Given the putative role of BMAA in neurodegenerative illnesses [37], these findings of widespread occurrence of BMAA in virtually all tested cyanobacteria at sometimes alarming high concentrations led to the assumption that BMAA may pose a worldwide significant risk to human health [34,38,39].…”
Section: Phycotoxinsmentioning
confidence: 90%